The Concept of Innovative Fiscal Policy: Theory and Empirical Evidence - Kovács, Olivér (Competitio, 2011)
This contribution addresses the question of what are the main constituents of an innovative fiscal policy in the context of sustainability. We apply the concept of sustaining and disruptive innovation to fiscal policy. On the one hand, innovative fiscal policy is able to be sustaining whereby public finance will incrementally improve without leaving its decisive structure. On the other hand, innovative fiscal policy should be disruptive as well in the context of long term sustainability, whereby the structure of public finances can be profoundly restructured as a reaction to future challenges. By using the Finnish recovery in the early 1990s, we can refine our argument about the use and necessity of the mixture of fiscal rules and independent institutions in favour of fiscal sustainability. We also shed light on the key sources of the expansionary consolidation that emerged in the aftermath of the fiscal adjustment in the early 1990s. We emphasise that innovative fiscal policy with a mixture of legislated fiscal rules and independent fiscal anchor is more likely to be associated with sustainability if the economy has weaker growth potential which does not provide enough social trust towards the consolidation efforts of the government.Journal of Economic Literature (JEL) classification: E61, E62, Q01